PENGARUH PENDAPATAN RUMAH TANGGA TERHADAP KONSUMSI DAGING BROILER DI KELURAHAN KLEAK KECAMATAN MALALAYANG MANADO - Putong, Mexen A; Kalangi, J K.J; Massie, M T; Lumi, T F.D (ZOOTEC, 2020)
THE EFFECT OF HOUSEHOLD INCOME ON BROILER MEAT CONSUMPTION AT  KLEAK URBAN VILLAGE OF MALALAYANG SUB DISTRICT  MANADO. The study was done to determine  the amount of broiler meat consumption in each household based on the level of household income at Kleak urban village  of Malalayang sub district in Manado. The survey was  used to get primary and secondary data. Primary data were taken from 30 samples of respondents obtained through interviews using the questionnaire.  Kleak is one among urban village in Malalayang Sub District with the total  of 806 households and consist of 2.705 population. Data Based on the variables and their measurements, the results of this study showed that income had the positive effect on broiler meat consumption of households on the Kleak urban village    Malalayang Sub District in Manado following the formulation, Y = 19368.49 + 0.013 X. This implied that as income increases per IDR  1  consumption increased by 0.013 kg assuming the other variables are fixed (ceteris paribus).